2015
DOI: 10.1186/s12893-015-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal implant removal: benefits and drawbacks – a patient survey

Abstract: BackgroundHardware removals are among the most commonly performed surgical procedures worldwide. Current literature offers little data concerning postoperative patient satisfaction. The purpose of our study was to evaluate the patients’ point of view on implant removal.MethodsWe surveyed patients of a German level one trauma center, who underwent hardware removal in 2009 and 2010, with regard to their personal experiences on implant removal. Exclusively, data obtained out of the survey were analyzed.ResultsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(123 citation statements)
references
References 27 publications
5
117
0
1
Order By: Relevance
“…Sanderson et al reported a complication rate of 19,7 % following removal of implants and the most common complication was infection (10). Reith et al found that impaired wound healing was the most common complication in their study (5). The majority of our complications occured due to previous pathologic conditions of implant removal such as infection, pseudoarthrosis, implant failure.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Sanderson et al reported a complication rate of 19,7 % following removal of implants and the most common complication was infection (10). Reith et al found that impaired wound healing was the most common complication in their study (5). The majority of our complications occured due to previous pathologic conditions of implant removal such as infection, pseudoarthrosis, implant failure.…”
Section: Discussionmentioning
confidence: 61%
“…Removal of the implant after internal fixation of bone fractures is one of the most commonly performed orthopedic operations (5). Implant removal surgery seems simple however, can lead to further complications such as; neurovascular injury, refracture, recurrence of deformity, delayed wound healing, new incident pain, broken implant, limitation in range of motion, wound infection, postoperative bleeding, incomplete removal (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, about 180,000 implants were removed in Germany, making this type of surgery the fourth most common orthopedic operation after fracture treatments, arthroscopic joint treatments and intervertebral disc interventions (Ochs et al, ). Reith et al () report on the results of a study with 332 patients in a German level‐one trauma center, where the complication rate associated with the removal of hardware was 10%. Depending on the study design, the implants and the location in the human body, other investigations have reported heterogeneous complication rates of up to 40% (Backes, Schep, Luitse, Goslings, & Schepers, ; Beaupre & Csongradi, ; Brown, Wheelwright, & Chalmers, ; Evers, Habelt, & Gerngroß, ; Minkowitz, Bhadsavle, Walsh, & Egol, ; Richards, Palmer, & Clarke, ; Stuby et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the study design, the implants and the location in the human body, other investigations have reported heterogeneous complication rates of up to 40% (Backes, Schep, Luitse, Goslings, & Schepers, 2013;Beaupre & Csongradi, 1996;Brown, Wheelwright, & Chalmers, 1993;Evers, Habelt, & Gerngroß, 2004;Minkowitz, Bhadsavle, Walsh, & Egol, 2007;Richards, Palmer, & Clarke, 1992;Stuby et al, 2012). According to the study of Reith et al (2015), the most frequent postoperative complications were wound healing disorders (36%), infections (21%), damage to neural tissue (14%), incomplete removal (12%), and other issues such as re-fracturing, bleeding, thrombosis, and keloid development (18%). In addition to the health risks of removal surgeries and the extended healing process, the socio-economic impact due to additional costs for hospitals and healthcare resources (Bostman & Pihlajamaki, 1996) as well as sick leave in a society's labor force (Busam, Esther, & Obremskey, 2006) is also mentioned in the literature.…”
mentioning
confidence: 99%
“…There is some evidence indicating that the postoperative complication rate depends on the specific localization of the implanted material [8].…”
Section: The Need Of Mechanically Competent Bioactive Implants For Bomentioning
confidence: 99%